Influence of process parameters on electrical discharge machined job surface integrity - Iqbal, A.K.M. Asif; Khan, Ahsan Ali (Science Publications, 2010)
Electrical Discharge Machining (EDM) is the most widely used non conventional machining process for removing material from workpiece by means of a series of repeated electric discharges. Electrical Discharge milling (ED-milling) is an emerging technology where a cylindrical tool electrode follows a programmed path in order to obtain the desired shape of a part. During machining of metals by EDM process, a large amount of heat is generated for which the surface characteristics of the metals are affected. This phenomenon is unavoidable but this can be controlled by suitable selection of the process parameters. Though in most of the cases only electrical parameters are chosen but non electrical parameters also play significant role in the area of surface integrity of the machined surface. The present study emphasized to establish a comprehensive analysis of surface integrity, including the micro cracks, recast layer thickness and material migration by combining both electrical and non electrical process parameters under a wide range of machining condition. Approach: In this research, experiment was designed by using design expert software (DOE). Response Surface Methodology (RSM) was used for designing the experiment. The process parameters varied in the present study were the rotational speed of the electrode (N), Voltage (V) and feed rate (f). Stainless steel AISI 304 was chosen as work material while a copper electrode was used for EDM milling operation. The EDM milling operations were performed on EDM machine mikrotools integrated multi process machine tools DT 110. In this research, Scanning Electron Microscope (SEM) was used to investigate the effect of machining parameters on recast layer thickness, micro cracks on the machined surface as well as the percentage of material migration on the workpiece surface. Results: Electrode rotation reduces recast layer thickness of about 16.58% than that of stationary electrode with same voltage and feed rate. Moreover, it was observed that migration of C and Cu on the workpiece surface reduces 8.8 and 60% respectively when using rotary electrode instead of stationary electrode with same parameters setting. Conclusion: These results indicated that voltage and rotary speed of electrode significantly affect various criteria of surface integrity. Electrode rotation helped to reduce micro cracks, recast layer thickness as well as migration of material became less when rotary electrode is used. Besides, the combination of reasonably low voltage and high rpm reduced micro cracks, recast layer thickness and minimized the surface contamination on workpiece surface during EDM milling of stainless steel.